Mogrol Regulates the Expression of ATPase Na+/K+ Transport Subunit 3, Inhibits Cardiomyocyte Apoptosis, and Plays a Protective Role Against Myocardial Infarction - Wang F; Zhou J; Liu W; Wang W; Tian B; Liu J; Zhang H; He P; Yang X; Yang L; Wang Y (Drug Design, Development and Therapy)
Feng Wang, Jinling Zhou, Weiwei Liu, Wei Wang, Boyan Tian, Jinyu Liu, Han Zhang, Peina He, Xiaoyun Yang, Li Yang, Yueheng Wang Echocardiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People’s Republic of ChinaCorrespondence: Yueheng Wang, Email 26500167@hebmu.edu.cnBackground: With the advancements in medical technology, the death rate from myocardial infarction (MI), a prevalent heart illness, has gradually decreased; however, treatment hurdles and diagnostic issues remain. Mogrol is a naturally occurring plant extract with specific biological activities such as antioxidant, anti-inflammatory, antitumor, and hypoglycemic effects. These biological activities make it a potential therapeutic drug or research subject; however, its function in MI remains unclear.Methods: Potential targets of mogrol were searched using the MI Disease Database through online databases. Among the three intersecting genes, we focused on ATPase Na+/K+ transporting subunit 3A3, which is expressed at low levels in patients with MI. The preventive effect of mogrol against MI was investigated using cardiac ultrasonography, Western blotting, qPCR assay, Cell counting kit-8, Ca2+ concentration measurement, Na+/K+-ATPase, and flow cytometry.Results: The findings demonstrated that mogrol upregulated Ca2+ concentration and ATPase Na+/K+ transporting subunit 3 protein levels in cardiomyocytes and tissues, downregulated the apoptosis-related proteins B-cell lymphoma 2-like protein 4, cleaved-caspase-3, and upregulated B-cell lymphoma 2. These effects enhanced cardiac function, prevented cardiomyocyte apoptosis, encouraged cardiomyocyte proliferation, and protected mice from MI. Knocking down ATP1A3 can reverse the protective effect of Mogrol.Conclusion: Mogrol may have a protective effect on myocardial infarction by regulating Ca2+ concentration and the level of the ATPase Na+/K+ transport subunit 3 protein, as well as by regulating apoptosis-related proteins. Further revealing the pharmacokinetics of mogrol in vivo is expected to make it a subsequent drug for the treatment of cardiac infarction.Keywords: mogrol, myocardial infarction, ATP1A3, apoptosis